Dogomo Makodo: Integrating Science, Movement, and Culture in A Student-Centered to Promote Health Literacy - Pratiwi, Febriana; Sarapung, Risky Richlos; Hazar, Fatih (JUMORA: Jurnal Moderasi Olahraga, 2025)
This study aims the effectiveness of the Dogomo Makodo program in enhancing health literacy among elementary school students by integrating physical education, science (IPA), and local wisdom in coastal Morotai. The program incorporates outdoor activities such as traditional games (Ban Laju, Gasing, and Jalan Sehat) and cultural practices like cooking Tabojou, aiming to deepen students’ understanding of health concepts, bodily functions, nutrition, and healthy living habits. Using a mixed-methods approach, the study involved 20 upper-grade elementary students. Data were gathered through pre-tests and post-tests to measure cognitive gains, along with Likert-scale questionnaires to explore students’ perceptions of the program. Results showed a significant improvement in students’ health knowledge and behaviors. The integration of science and physical education provided a meaningful, engaging, and contextual learning experience. Moreover, the use of local cultural elements not only strengthened students’ emotional engagement and identity but also extended the learning impact into their homes and communities. The Dogomo Makodo model demonstrates an innovative, student-centered educational approach that aligns with the Merdeka Curriculum. It is recommended for replication in other rural and culturally diverse settings to support nationwide efforts in promoting health literacy at the primary education level.